Tradeoffs over rate cycles: Activity, inflation and the price level - Kristin Forbes; Jongrim Ha; M. Ayhan Kose (Koç University-TÜSIAD Economic Research Forum (ERF), 2025)
Central banks often face tradeoffs in how their monetary policy decisions impact economic activity (including employment), inflation and the price level. This paper assesses how these tradeoffs have evolved over time and varied across countries, with a focus on understanding the post-pandemic adjustment. To make these comparisons, we compile a cross-country, historical database of "rate cycles" (i.e., easing and tightening phases for monetary policy) for 24 advanced economies from 1970 through 2024. This allows us to quantify the characteristics of interest rate adjustments and corresponding macroeconomic outcomes and tradeoffs. We also calculate Sacrifice Ratios (output losses per inflation reduction) and document a historically low "sacrifice" during the post-pandemic tightening. This popular measure, however, ignores adjustments in the price level-which increased by more after the pandemic than over the past four decades. A series of regressions and simulations suggest monetary policy (and particularly the timing and aggressiveness of rate hikes) play a meaningful role in explaining these tradeoffs and how adjustments occur during tightening phases. Central bank credibility is the one measure we assess that corresponds to only positive outcomes and no difficult tradeoffs.
Keywords: E31; E32; E43; E52; E58; F33; F44; N10; 330; monetary policy; interest rates; central bank; Sacrifice Ratio; business fluctuations; prices; employment